Nepal in the Vortex of Modernity: A Study of Lain Singh Bangdel’s Muluk Bahira - Paudel, Maheswor (Myagdi Guru, 2025)
This article explores how Lain Singh Bangdel’s Muluk Bahira (1963) portrays Nepali modernity through the experiences of migrant characters, with a view to probing into the tensions between tradition and modernity in early twentieth-century Nepal. It aims to observe how migration to modern Indian cities shapes Nepali identity, focusing on how modernity is both an opportunity and a source of alienation. Primarily, applying a literary analysis framework, this study derives impetus from Anthony Giddens’ concept of modernity as “a post-traditional order”, Arjun Appadurai’s notion of migration creating “imaginaries of modernity”, Michael Hutt’s observation of Nepali modernity as “a tragic oscillation between aspiration and loss”, and Pratyoush Onta’s view of Nepali modernity as a “contested space where global influences intersect with local practices”. Through close reading of the novel supported by the theoretical ideas, this article assesses the activities of the main characters Rane, Myauchi, Mahila Bhujel, and Dal Bahadur in modern cities like Darjeeling, and analyzes their transnational mobility, and interactions with diverse global communities. On the basis of the analysis, the article reaches the conclusion that Bangdel in Muluk Bahira illustrates modernity as a vortex, where aspirations for prosperity are intercepted by separation, loss, and cultural dislocation. This study contributes to understanding Nepali literature’s engagement with modernity, highlighting how Muluk Bahira captures the socio-cultural dynamics of early twentieth-century Nepali migration. Future research could explore deeper analyses of Muluk Bahira and other Nepali literary texts to see how they encapsulate the themes of migration and modernity, portraying the characters that navigate transnational locations.